Perlindungan Karya Cipta Video Dalam Rangka Proses Pembelajaran Online: Perspektif Hak Ekslusif Pencipta - Rafika Amalia; Putu Aras Samsithawrati (Jurnal Magister Hukum Udayana (Udayana Master Law Journal), 2022)
The purpose of this study is to analyze the regulation on the ownership of the exclusive right of a video, as copyright work, created by scholars in the online learning process and its protection system. This study uses a normative legal research method with the statute as well as analytical and conceptual approaches. The results indicate that normatively the video created by scholars in online learning is not included under the scope of Articles 35 and 36 Law 28,2014 (Copyright Law). However, if the video created by the scholar is the result of an assignment in online learning under the leadership and supervision that involves a process of guidance, direction, or correction from the person who designed and assigned it (lecturer), it can be interpreted that the video meets the criteria of Article Copyright Law, where the Author is the person who designed the work, in this case, the lecturer. Meanwhile if the video (created from the assignment in the online learning process) aims to increase the creativity and thought of the scholars and where the originality and ideas are entirely the results of the intellectual creativity of the scholars, it can be interpreted as fall under Article 1(2) Copyright Law. Thus, the scholars can be considered the Author who has exclusive rights to the video. The copyright protection system adheres to an automatic protection system, where recording is not an obligation but it is important to implement it. Tujuan dari penelitian ini untuk menganalisis pengaturan kepemilikan hak eksklusif atas karya cipta video yang dihasilkan para penstudi dalam proses pembelajaran daring dan sistem perlindungannya. Penelitian ini menggunakan metode penelitian hukum normatif dengan pendekatan Perundang-Undangan dan Analisis Konsep Hukum. Hasil penelitian menunjukkan bahwa secara normatif, karya cipta video yang dihasilkan para penstudi dalam proses pembelajaran daring tidak termasuk dalam lingkup Pasal 35 dan 36 Undang-Undang Nomor 28 Tahun 2014 (UUHC). Namun, jika video yang dibuat penstudi tersebut dihasilkan dari suatu penugasan pembelajaran daring di bawah pimpinan dan pengawasan yang melibatkan proses bimbingan, pengarahan, ataupun koreksi dari orang yang merancang sekaligus menugaskan (dosen) maka dapat ditafsirkan karya cipta video itu memenuhi kriteria Pasal 34 UUHC dimana Pencipta adalah orang yang merancang Ciptaan, dalam hal ini dosen. Sedangkan jika video yang dihasilkan dari penugasan dalam proses pembelajaran daring untuk meningkatkan kreatifitas dan olah pikir para penstudi dimana originalitas dan idenya adalah seutuhnya hasil kreatifitas intelektual penstudi maka dapat ditafsirkan memenuhi unsur Pasal 1(2) UUHC. Dengan demikian Penstudi dapat dianggap sebagai Pencipta yang memiliki hak eksklusif atas video tersebut. Sistem perlindungan hak cipta menganut automatically protection system, dimana pencatatan bukanlah kewajiban namun penting untuk dilakukan.